The pharmacodynamics of epidural blockade with 0.5% ropivacaine and varying concentrations of glucose among patients for major gynecologic surgery a randomized, double-blind, placebo controlled study - Calimag, Maria Minerva P.
Objectives: The aim of this study is to determine the effect of varying concentrations of glucose (0%, 0.42%, 0.83% and 1.25%) on the onset, maximal spread and two-segment regression of 0.5% ropivacaine (20 mL) injected into the epidural space through the L2-3 ot L3-4 interspace. Design: Randomized, double-blind,placebo-controlled clinical trial. Setting: The University of Santo Tomas Hospital, a tertiary teaching hospital. Participants: Thirty-two (32) female patients with a mean age of 42.9 (+ 10.42 SD) years, mean height of 153.8 (+ 2.32 SD) cm and mean weight of 58.7 (+11.36 SD) kg, scheduled to undergo major gynecologic procedures in the lower abdomen were enrolled from August 11, 2000 to October 31, 2000. Methods: After obtaining Institutional Review Board approval and patient's written informed consent, patients who met the inclusion criteria, were assigned by block randomization into four groups (Group I - 0%, Group II - 0.42%, Group III - 0.83% and Group IV - 1.25%) and given epidural anesthesia with the ropivacaine-glucose mixture. Statistical Analysis: Pitcomes measures were time to onset, maximal spread and two-segment regression of sensory, motor and sympathetic blocks. Statistical analyses were One-Way ANOVA with Bonferroni Post Hoc Multiple Comparisons Test or repreated measures ANOVA with Dunnett Post Hoc Multiple Compraisons Test of quantitative variables, and chi-sqaure analyses or Fisher's exact test of qualitative variables. Outcomes with tw0-tailed P values les than or equal to 0.001 were considered statistically significant. For all patients randomized on whom not all outcomes can be determined, "intent-to-treat" analyses was done. Population pharmacodynamic analysis was done to determine the time course of local anesthetic action in the epidural space. Results: The estimates of the population mean parameters (standard deviation) were as follows: (1) mean onset time; that is, time to reach T12: Group I = 4.13 + 1.81 min (n=8); Group II = 4.13 + 1.25 min (n=8); Group III = 5.50 + 1.07 min (n=8); Group IV = 6.38 + 1.15 min (n=8); (2) the mean maximal achieved level was T4 (n=8), for all the groups; (3) the mean time to maximal level for the different groups were: Group I = 19.88 + 12.90 min (n=8); Group II = 10.13 + 1.55 min (n=8); Group III = 20.63 + 2.00 min (n=8); Group IV = 26.13 + 3.64 min (n=8); (4) the mean duration of effect: Group I = 213.75 + 53.17 min (n=8) Group II = 190.00 + 41.40 min (n=8); Group III = 236.62 + 39.02 min (n=8); Group IV = 206.88 + 39.46 min (n=8); (5) rate of onset of sensory effect: Group I = 0.1470 (n=8) min -1; Group II = 0.2032 (n=8) min -1; Group III = 0.1232 (n=8) min -1; Group IV = 0.1073 (n=8) min -1; (6) rate of offset of sensory effect: Group I = 0.006823 (n=8) min -1; Group II 0.008093 (n=8) min -1; Group III = 0.006856 (n=8) min -1; Group IV = 0.1073 (n=8) min -1; (6) rate of offset ogf sensory effect: Group I = 0.006823 (n=8) min -1; Group II = 0.008093 (n=8) min -1; Group III = 0.006856 (n=8) min -1; Group IV = 0.000088 (n=8)min -1. Discussion: The time to achieve maximal sensory spread to T4 and motor blockade to Bromage 3 was significantly faster with more uniform spread and less variability among patients in Group II - 0.42% (density = 1.011; pH=4.83) as compared to solutions without glucose (Group I - 0%; density = 1.004; pH = 5.38) and those with higher glucose concentrations (Group III - 0.83%; density = 1.015; pH = 4.42 and Group IV - 1.25% density = 1.020; pH = 4.17) which showed longer mean times to achieve maximal sensory and motor blockade with more variability producing less predictable spread. Once established however, all blocks produced by glucose-containing solutions in Groups II, III and IV are denser with more profound symphathetic blockade manifested as a 20% fall in all cardiovascular parameters. Conclusion: In no-pH buffered mictures of ropivacaine and varying concentrations of glucose, no dose-response relationship between the glucose concentration and the mean time to achieve sensory and motor blockade was observed. Statistically and clinically significant outcomes were obtained even with low glucose concentrations of 0.42%. At this concentration, the anesthetic solution has a density of 0.011 and a pH of 4.83.
Theses--(Master of Science in Epidemiology-Clinical Epidemiology) UPCM
Keywords: Generative organs, Female--Surgery.; Glucose